DRUG NEPHROPATHY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In recent years, the number of drug-induced kidney lesions in the practice of doctors of all specialties has significantly increased. The reason is the continuous expansion of the arsenal of medicines. In some European countries, complications of drug therapy occur in 30% of patients who are in the hospital. Of these, 25% of these complications are the cause of death.